2015
DOI: 10.7763/ijcea.2015.v6.453
|View full text |Cite
|
Sign up to set email alerts
|

Study of Heavy Elements and Radioactivity Concentrations in Some Eye Cosmetics Commonly Used in Arabic Regions

Abstract: Abstract-Thirteen samples of eye cosmetics including five samples of artificial eye cosmetics and eight samples of traditional eyeliner (kohl) were collected from various Arabic markets, and analyzed using inductively coupled plasma-optical emission spectrometer (ICP-OES) to assess concentrations of the most toxic elements (arsenic (As), cadmium (Cd), mercury (Hg) and lead (Pb)), and high purity germanium detector (HPGe) to determine radioactivity concentrations of the natural radionuclides 238 U, 235 U, 226 R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
1
1
Order By: Relevance
“…Comparing with the other available Fundamental and applied physics measurements its very low than the results of 7.9-37.6 Bq/Kg estimated in reference [25]. In the kohl sample, the radium concentration is 0.105 Bq/Kg which is lower than 0.866 Bq/Kg the results of reference [26]. The obtained results of cosmetics samples showed that, the samples have different concentrations for radon or radium from one type of cosmetic to another, due to its producing composition materials which need to another investigation tools not available here, to know the materials that increase the radiation concentration.…”
Section: Discussioncontrasting
confidence: 48%
“…Comparing with the other available Fundamental and applied physics measurements its very low than the results of 7.9-37.6 Bq/Kg estimated in reference [25]. In the kohl sample, the radium concentration is 0.105 Bq/Kg which is lower than 0.866 Bq/Kg the results of reference [26]. The obtained results of cosmetics samples showed that, the samples have different concentrations for radon or radium from one type of cosmetic to another, due to its producing composition materials which need to another investigation tools not available here, to know the materials that increase the radiation concentration.…”
Section: Discussioncontrasting
confidence: 48%
“…A research carried on a different samples of eye kohl collected from state of Libya, Egypt and Kingdom of Saudi Arabia (KSA) and the results indicate that kohl samples are contaminated with a significant concentrations of semi and heavy metals such as As, Cd, Hg, and Pb [24]. In United Arab Emirates (UAE), a survey of minerals was carried out for 53 kohl samples.…”
Section: Introductionmentioning
confidence: 99%